Comforting or rewarding myself: Choices for self-gifting. Issue 4 (1st October 2016) - Hur, Hee Jin; Choo, Ho Jung
Abstract: This study aimed to empirically explore consumers' preferred self-gift products depending on the motivation to give self-gifts. Perceiving the distinctive motivations for self-gifts led to the postulation of likely distinctiveness in selecting types of attractiveness-relevant products (enhancing vs. problem-solving products) for self-gifts. Two empirical studies were conducted to test the hypotheses with 319 female consumers in their 20s and 30s. Study 1 was an experiment through which different preferences were tested and verified. Here, two types of attractiveness-relevant products showed differing preference levels when the motivation was to give a self-gift reward, thus representing a therapeutic motive. This study also revealed that among enhancing and problem-solving products, experiential products and material products showed different levels of preferences. Study 2 was conducted to provide empirical evidence of the moderating effect of regulatory focus on product type preferences and self-gift motivation. This study expanded the scope of the research in this field as it examined consumer behaviors regarding self-gifts and linked consumer motivations to give self-gifts with relevant product types. We also clarified that different situations exist for self-gift consumption and the preferred products vary depending on a consumer's motivation to give a self-gift.